Comportamiento microestructural de una aleación TI - 6 AL - 4 V empleada en pulpa lixiviada//Behaviour microstructure of an alloy TI - 6 AL - 4 V used in leached pulp - Rodney E. Correa‐Suárez; Tomás Fernández-Columbié; Isnel Rodríguez‐González; Dayanis Alcántara‐Borges (Ingeniería Mecánica, 2014)
En el trabajo se determina el comportamiento microestructural de la aleación Ti - 6 Al - 4 V del tipo α + β de la cual se fabrica el cuerpo de las válvulas que trabajan en la línea de pulpa lixiviada, que por efecto del fluido sufren perforaciones y son recuperadas por proceso de soldadura, en el establecimiento del ciclo térmico de soldadura se tuvo en cuenta la intensidad de corriente, el voltaje del arco eléctrico, la velocidad de soldadura y la energía lineal del proceso de soldadura. Como material de aporte se seleccionó el electrodo consumible ERTi – 2. De la válvula dañada se seleccionaron muestras de diferentes zonas, las cuales se caracterizaron en dependencia con la afectación de la pulpa lixiviada caliente. Palabras claves: pulpa lixiviada, ciclo térmico, microestructural, titanio, isotermas. ______________________________________________________________________________ Abstract In this article, we study various solution schemes reported in the literature, which deal with the problem of irregular parts distribution on flat surfaces with two-dimensional nesting. Different solution schemes were analyzed, which they consider to be the real geometry of the part, during the evaluation and positioning them on the surface to be cut, ensuring the best use of the material. The proposed scheme is characterized by a graphic treatment of the pieces that can accelerate the process of recognition and evaluation of options coupling between them, as well as the creation of cluster populations growing to its final location on the surface to be cut. In the generation of populations of possible solutions, using an algorithm based on the method of integration variables, in addition is made comparing the results obtained by the proposed method with other results generated by procedures developed by different authors, achieving improved use. Key words: leached pulp, cycle thermal, microstructure, titanium, isotherm.